Process Practice for Production of Steel H11Mn2SiA for Welding Wire by 65 t Consteel EBT EAF-LF-CC Flowsheet at Shiheng Steel - Li Hongyong; Chai Jianming (Teshugang, 2007)
With  using  60%  hot  metal  +  quality  scrap  charge,Consteel  EAF  eccentric  bottom  tapping  operation,con- trolling    tapping    end [C]    0.035%～0.050%    and    tapping[P]≤0.012%,LF    refining    by    low    basicity    slag,feeding silicon  wire,  soft  blown  argon  for  15  min  after  LF  refining  and  fully  shielding  auto  control  casting  150  mmx150  mm  bilet  in whole period,  the  average oxygen  content  in steel  H11Mn2SiA(0.06~0.09C,0.82～1.00Si,1.45~1.70Mn)for welding  wire  was  20×10-6of which  the  Φ5.5  mm  wire  rods  could  be  direct  drawn  to  φ1.0  mm  wire  without  by  heat  treatment and  no-broken  wire   occurred.